THE EFFECT OF TUMOR NECROTIC FACTOR ALPHA POLYMORPHISM ON RESPONSE TO BIOLOGICAL TREATMENT FOR RHEUMATOID ARTHRITIS PATIENTS (Iraqi Journal of Medical Sciences, 2017)
Background: The tumor necrotic factor alpha (TNF-?) was associated with rheumatoid arthritis (RA) pathogenesis and inflammation of joint, for this consider important target for drugs (TNF inhibitors) as for example infliximab.Objective: To investigate the role of TNF-?-308 polymorphism G>A in unresponsiveness to biological treatment (infliximab) in RA patients.Methods: This study included 29 RA patients treated with infliximab attending Department of Rheumatology in Baghdad Teaching Hospital and diagnosed according to American College of Rheumatology (ACR) with 30 persons as healthy controls. The age range was 20 to 68 years. The DAS28 was calculated for each RA patients. Blood samples were taken from them during the period from May 2014 to January 2015. The blood samples were tested by polymerase chain reaction (PCR) for TNF-?-308 G>A then by restriction fragment length polymorphism (RFLP) for A allele and G allele. HLA-DR genotyping by PCR-SSO.Results: The frequency of A allele was 23 (39.7%) in RA patients while G allele was 35 (60.3%) in RA patients, whereas in in controls A and G alleles frequencies were 5 (8.3%) and 55 (91.7%) respectively. The A allele was associated with high DAS28 19 (82.6% while for G allele was 1 (2.9%) and DAS28 showing significant association with TNF-?-308 polymorphism G>A. The distribution of A allele in female RA patients was 16 (36%) whereas G allele was 28(64%), while in male RA patients, A and G allele were 7 (50%) for each of them. The HLA-DRB1 not showing significant association with TNF-?-308 polymorphism G>A.Conclusion: The TNF-?-308 polymorphism G>A has effect on response to biological treatment (infliximab). The A allele of TNF-? was associated with unresponsiveness to infliximab and RA patients who carry this allele have high DAS28 score. The HLA-DRB1 not showing association with TNF-?-308 polymorphism G>A.Keywords: RA, TNF-? polymorphism, infliximab, HLA-DR.Citation: Hachim Sk, Abbas AA, Alosami MH. The Effect of tumor necrotic factor alpha polymorphism on response to biological treatment for rheumatoid arthritis patients. Iraqi JMS. 2017; Vol. 15(3): 220-226. doi: 10.22578/IJMS.15.3.2
Keywords: RA; TNF polymorphism; infliximab; HLADR